2005
DOI: 10.5381/jot.2005.4.1.a6
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Superstructure for UML.

Abstract: A key aspect of successfully using UML is understanding the semantics of the notations. UML 2 will increase the already substantial collection of notations supported by UML 1.x. At the same time, this will augment the difficulty users experience in understanding semantics. In this paper we propose that while the diverse notations may render concepts differently, the concepts can often be considered semantically equivalent. This gives rise to an architecture where two single abstract syntaxes (structure and beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Its usage is mostly limited to a class diagram, sometimes extended with OCL for specifying rules on top of the classes. Some studies, e.g., Clark et al (2003), Cuadrado and Molina (2009), Evans (1999), Evans et al (2003), use packages and package diagrams to model relations between domains.…”
Section: Methods Engineeringmentioning
confidence: 99%
“…Its usage is mostly limited to a class diagram, sometimes extended with OCL for specifying rules on top of the classes. Some studies, e.g., Clark et al (2003), Cuadrado and Molina (2009), Evans (1999), Evans et al (2003), use packages and package diagrams to model relations between domains.…”
Section: Methods Engineeringmentioning
confidence: 99%
“…The BON and Eiffel versions have an advantage due to their component-based style of specification and their use of patterns. However, even using good object-oriented design practice may be insufficient for promoting extensibility and wholesale modification, for instance, as suggested with the pUML proposal for UML 2.0 [Evans et al 2005], which recommended adding templates and frameworks as first-class language concepts. -Constructed via Tools is the degree to which tools are available to assist in constructing the specification (e.g., diagramming tools, smart editors with syntax checking and highlighting, autocode generation).…”
Section: Overall Comparisonmentioning
confidence: 99%
“…Metamodeling is now accepted as a critical part of the design of modeling languages [Evans et al 2005]: without a precise, consistent, and validated metamodel specification, it is difficult to explain a language, build tools to support it and produce consistent and unambiguous models. The importance of metamodeling is reflected in the literature, for example, the recent workshop on metamodeling for support of MDA [Evans et al 2003], the substantial effort placed on reengineering the metamodel of UML for version 2.0 [Object Management Group 2004b], the emphasis on metamodeling in Eclipse via the Eclipse Modeling Framework [Budinsky et al 2003] and the focus of the EU Integrated Project MODELWARE, wherein metamodeling pervades all aspects of the project.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting case for this approach is UML, which consists of different languages supporting different modelling viewpoints. As is shown in [6], these languages can be divided into two main categories: structural languages (for class and component diagrams) and behavioural languages (for use case, collaboration, state, activity and sequence diagrams). Furthermore, it is shown that for each of these categories a basic conceptual model can be defined.…”
Section: Example Applications Of the Extended Profiles Packagementioning
confidence: 99%